The sorption of monovalent cations onto norway spruce: Model studies using wood flour and LiCl solution. (4th March 2017) - Kolavali, Reddysuresh; Hasani, Merima; Theliander, Hans
Abstract : The transport of chemicals in a porous material such as wood is very complex and involves several processes: the diffusion of chemicals in the cell pores (lumen and pit pores), through the cell walls at certain conditions, and sorption of wood tissue. In the present study, batch sorption experiments were performed to examine the sorption of Li + ions from an aqueous LiCl solution onto Norway spruce wood flour samples. The experimental methodology employed is suitable for differentiating the amount of ions sorbed onto the wood tissue and dissolved in the solution in wood pores. The apparent equilibrium sorption data were analyzed using two widely applied isotherm models: Langmuir and Freundlich. The results suggest that the sorption was spontaneous, and for the experimental conditions studied, probably involved several interaction types between the different functional groups of the wood and the Li + /Cl − ions.